Position change during colonoscopy improves caecal intubation rate, mucosal visibility, and adenoma detection in patients with suboptimal caecal preparation - Vijaypal Arya; Shikha Singh; Shashank Agarwal; Ashok Valluri; Oonagh Dowling; Cristina Sison; Kalpana Arya Gupta (Gastroenterology Review)
Introduction : Most colonoscopies are completed in the left lateral (LL) position but in cases of suboptimal caecal preparation, changing the patient’s position to supine (S) and, if needed, to right lateral (RL) improves caecal intubation rate, mucosal visibility, and adenoma detection. Aim : To determine if position change during colonoscopy facilitates optimal visualisation of the caecum. Material and methods : A total of 359 patients were grouped into three categories based on the initial caecal intubation position. After caecal intubation, caecal visibility was scored on a four-point scale depending on the number of imaginary quadrants of the caecum completely visualized – Arya Caecal Prep Score. A score of 1 or 2 was unsatisfactory, while 3 or 4 was considered satisfactory. In patients with unsatisfactory score, position was changed from LL to S and then RL and visibility was scored again. Results : The initial caecal intubation in the LL position was achieved in 66.8% of patients, S in 28.5%, and RL in 4.8% of patients. 84.5% (300/355) of patients had an acceptable visualisation score at the initial caecal intubation position. Of the 55 patients with unsatisfactory caecum visualisation scores in the initial intubation position, 30 (8.5%) had satisfactory scores after the first position change (95% CI: 5.77–11.84). Twenty-five (7.04%) subjects required two position changes (95% CI: 4.61–10.22%). An additional 9.3% (11/118) of adenomas were detected in caecum and ascending colon following position change. Conclusions : Changing patient position improves caecal intubation rate, mucosal visibility, and adenoma detection.